A systems approach to enabling affordable housing for migrants through upgrading Chengzhongcun: A case of Xiamen. (October 2020) - Tian, Li; Yao, Zhihao; Fan, Chenjing; Zhou, Lin
Highlights: As informal settlements, Chengzhongcun has accommodated numerous migrants whose housing rights have been ignored. Property-led redevelopment of Chengzhongcun has deprived migrants of low-cost housing. Linking Chengzhongcun renewal and provision of public rental housing can help provide affordable housing for migrants.